Circulating serum interleukin-6, serum chitinase-3-like protein-1, and plasma vascular endothelial growth factor are not predictive for remission and radiographic progression in patients with early rheumatoid arthritis: post-hoc explorative and validation studies based on the CIMESTRA and OPERA trials. (4th July 2018) - Brahe, CH; Dehlendorff, C; Østergaard, M; Johansen, JS; Ørnbjerg, LM; Hørslev-Petersen, K; Stengaard-Pedersen, K; Junker, P; Ellingsen, T; Lindegaard, H; Hansen, I; Lottenburger, T; et al.
Abstract : Objective : To investigate serum interleukin-6 (IL-6), serum chitinase-3-like protein-1 (YKL-40), and plasma vascular endothelial growth factor (VEGF) as measures of disease activity and predictors of clinical remission and radiographic progression in two early rheumatoid arthritis (RA) randomized controlled trials (RCTs). Method : Treatment-naïve patients with early RA (< 6 months' duration) and active disease, participating in two investigator-initiated RCTs, were treated according to a predefined treat-to-target algorithm aiming at inflammatory control, using methotrexate (MTX) + cyclosporine versus MTX + placebo (CIMESTRA study, n = 150, 5 year follow-up) or MTX + adalimumab versus MTX + placebo (OPERA study, n = 180, 2 year follow-up). The 28-joint Disease Activity Score (DAS28) and conventional radiography [bilateral hands and feet at baseline, 2 years and 5 years (only CIMESTRA)] were obtained at baseline and during follow-up. Serum IL-6, serum YKL-40, and plasma VEGF were measured in baseline blood samples and during follow-up. Hypotheses regarding the biomarkers' relation with DAS28 and ability to predict clinical remission (DAS28 < 2.6) and radiographic progression (change in total Sharp van der Heijde score ≥ 2) were generated in CIMESTRA and validated in OPERA, by Spearman's correlation and logistic regression analyses. Results : Baseline IL-6, YKL-40, and VEGF correlated significantly with DAS28 in CIMESTRA (r = 0.50, r = 0.36, r = 0.36, respectively, all p < 0.01) and these results were confirmed in OPERA patients (r = 0.52, p < 0.01; r = 0.18, p = 0.01; r = 0.23, p = 0.002, respectively). None of the biomarkers (absolute values or change) was predictive of clinical remission or radiographic progression at 2 or 5 years in either study. Conclusion : Serum IL-6, serum YKL-40, and plasma VEGF were significantly correlated with DAS28 at baseline, but did not have consistent predictive value for clinical remission or radiographic progression in two early RA RCTs.